If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -28)(15 + -1x) = 0 Reorder the terms: (-28 + 5x)(15 + -1x) = 0 Multiply (-28 + 5x) * (15 + -1x) (-28(15 + -1x) + 5x * (15 + -1x)) = 0 ((15 * -28 + -1x * -28) + 5x * (15 + -1x)) = 0 ((-420 + 28x) + 5x * (15 + -1x)) = 0 (-420 + 28x + (15 * 5x + -1x * 5x)) = 0 (-420 + 28x + (75x + -5x2)) = 0 Combine like terms: 28x + 75x = 103x (-420 + 103x + -5x2) = 0 Solving -420 + 103x + -5x2 = 0 Solving for variable 'x'. Factor a trinomial. (-15 + x)(28 + -5x) = 0Subproblem 1
Set the factor '(-15 + x)' equal to zero and attempt to solve: Simplifying -15 + x = 0 Solving -15 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + x = 0 + 15 Combine like terms: -15 + 15 = 0 0 + x = 0 + 15 x = 0 + 15 Combine like terms: 0 + 15 = 15 x = 15 Simplifying x = 15Subproblem 2
Set the factor '(28 + -5x)' equal to zero and attempt to solve: Simplifying 28 + -5x = 0 Solving 28 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-28' to each side of the equation. 28 + -28 + -5x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + -5x = 0 + -28 -5x = 0 + -28 Combine like terms: 0 + -28 = -28 -5x = -28 Divide each side by '-5'. x = 5.6 Simplifying x = 5.6Solution
x = {15, 5.6}
| D-4=20 | | x^2-46x+433=0 | | 2(4+f)=8 | | 3x^6-39x^5-90x^4= | | 5(x+9)=x | | 1x(-4)-8x9/-3 | | (X+50+2x-12)= | | (-19)-(-7)-(-18)= | | (X+50+2x-23)= | | -5(v+2)=5v-5+3(2v+3) | | 50.25=1.25t | | (2x+y)(2x+y)(2x+y)(2x+y)(2x+y)=1024 | | 5x/2=2 | | 8x+26y=180 | | 2(7x+4)=8 | | (x^7+3y^8)(-5x^9+4y^2)= | | 6+2(4w-2)=-2(3w-6)+8w | | 8t^10-88t^9-208t^8= | | ((x^2)/(4))((xy/6)^-1)((2y^)/(x)) | | v^2+4vp-21p^2= | | 50+1.75x=39.99+250x | | 4+5s-1=6s+8-2s | | 3x+(2x-3)=12 | | -6(6-2x)=-108 | | 9x^7+9x^6-180x^5= | | 96x-.06x^2=0 | | -2(9w-3)+6w=-2(w+4) | | 4/3=(-6e)-5/3 | | g(x)=3x^3-x^2-7x | | x-46=49 | | 5(v-1)-3=-4(-4v+1)-5v | | 5000000=1.36x^2+27.8x+304 |